PENGEMBANGAN SISTEM KASIR BERBASIS WEB DI NATTA COFFEE: STUDI IMPLEMENTASI FRAMEWORK LARAVEL - Rusmara, Rafi Hafizqalma (Universitas Lampung, 2025)
Abstract. The development of a web-based cashier system for Natta Coffee aims to improve efficiency in managing sales transactions, stock recording, and financial reports. A web-based cashier system was chosen because it provides flexible access without device limitations, allows real-time business management, and minimizes the risk of data loss compared to conventional manual or desktop-based systems. The use of the Laravel framework in this development is based on its advantages in security, efficiency, and ease of code management through the MVC (Model-View-Controller) concept. This research adopts the Rapid Application Development (RAD) method, enabling fast system development with flexible iterations based on user needs. The test results show that the developed cashier system improves transaction recording accuracy, speeds up the payment process, and provides automated financial reports. With this system, Natta Coffee can optimize its business operations and enhance service quality for customers.Abstract. The development of a web-based cashier system for Natta Coffee aims to improve efficiency in managing sales transactions, stock recording, and financial reports. A web-based cashier system was chosen because it provides flexible access without device limitations, allows real-time business management, and minimizes the risk of data loss compared to conventional manual or desktop-based systems. The use of the Laravel framework in this development is based on its advantages in security, efficiency, and ease of code management through the MVC (Model-View-Controller) concept. This research adopts the Rapid Application Development (RAD) method, enabling fast system development with flexible iterations based on user needs. The test results show that the developed cashier system improves transaction recording accuracy, speeds up the payment process, and provides automated financial reports. With this system, Natta Coffee can optimize its business operations and enhance service quality for customers.